Risiko-Renditeprofil des neuen Covered-Call-Index der Deutschen Börse - Patrick Behr; Hartmut Graf; André Güttler (Kredit und Kapital, 2008)
– Risk-Yield Profile of the New Covered-Call-Index of the German Stock Exchange We have analysed in this article the risk-yield profile of the new DAXplus Covered-Call-Index of Deutsche Börse AG (German Stock Exchange) in the period from January 1993 to June 2005. It has turned out that, on a risk-adjusted basis, investing in DAXplus Covered Call Certificates was preferable to any direct investment in the DAX in the period under review. One of the reasons justifying this conclusion has been that the implied volatilities of DAX-based call options were too high compared with the historical volatilities and have resulted in excessive option premiums. We have also analysed the implications of several moneynesses and residual lifetimes of certificates for the risk-yield profile of covered call strategies and of the DAX. The DAXplus Covered Call can, as distinct from other covered call strategies, legitimately claim to have experienced the most favourable development in the period under review. In conclusion, we have compared the DAXplus Covered Call with three covered call strategies based on international stock indices. Measured by the Stutzer index, the DAXplus Covered Call shows that its risk-adjusted performance has been best.
Keywords: 330